2016
DOI: 10.1161/circep.115.003807
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Outcomes of Postrandomization Atrial Tachyarrhythmias in the Resynchronization/Defibrillation in Ambulatory Heart Failure Trial

Abstract: Background— Whether adding cardiac resynchronization therapy (CRT-D) to an implanted cardioverter–defibrillator alters the risk of atrial fibrillation or other atrial tachyarrhythmias (AF/AT), or if postimplantation AF/AT modulate the benefits of CRT-D, remain unknown. Methods and Results— We studied 972 Resynchronization/Defibrillation in Ambulatory Heart Failure Trial (RAFT) participants without permanent AF, who were randomized to CRT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Many observational studies have suggested that CRT reduced AF, whereas some of the large CRT clinical trials (CARE HF and MADIT CRT) failed to demonstrate a significant reduction in the burden of AF 7,27 . RAFT even suggested an increase in AF in the CRT arm, although CARE HF and RAFT used clinical AF rather than device‐detected AF 9 . This study has demonstrated significant reductions in AF in patients with aCRT programmed ON.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Many observational studies have suggested that CRT reduced AF, whereas some of the large CRT clinical trials (CARE HF and MADIT CRT) failed to demonstrate a significant reduction in the burden of AF 7,27 . RAFT even suggested an increase in AF in the CRT arm, although CARE HF and RAFT used clinical AF rather than device‐detected AF 9 . This study has demonstrated significant reductions in AF in patients with aCRT programmed ON.…”
Section: Discussionmentioning
confidence: 69%
“…Perhaps the more physiological AV intervals may explain the benefit of the algorithm. The RAFT investigators postulated that overly short programming of AV intervals may explain their observation of increased AF with CRT 9 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations